2017
DOI: 10.4136/ambi-agua.2086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sagittaria montevidensis Cham. & Schltdl. as a bioindicator and phytoextractor of toxic metals

Abstract: This study evaluated the bioindication and phytoremediation capacity of the aquatic macrophyte Sagittaria montevidensis by using it to assess the bioconcentration and translocation of heavy metals. A simple sampling was conducted at four sites in the region of Pelotas, southern Brazil, where plants, water and sediments were collected. The plants were subjected to nitric-perchloric acid digestion and the sediments underwent pseudo-total acid digestion. The determination of the elements Cr, Cu, Pb, Ni and Zn in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…TF >1 was obtained for Cu and Ni, behaving as a metal accumulator for these elements. The TFs for Cu, Ni and Zn obtained in this work were lower than those reported by Kickhöfel Ferrer et al [16] for this species. For Cr and Pb they were similar to those detected by Demarco et al [23] (0.4 and 0.5, respectively).…”
Section: Heavy Metals In Plant Tissuecontrasting
confidence: 83%
See 3 more Smart Citations
“…TF >1 was obtained for Cu and Ni, behaving as a metal accumulator for these elements. The TFs for Cu, Ni and Zn obtained in this work were lower than those reported by Kickhöfel Ferrer et al [16] for this species. For Cr and Pb they were similar to those detected by Demarco et al [23] (0.4 and 0.5, respectively).…”
Section: Heavy Metals In Plant Tissuecontrasting
confidence: 83%
“…The highest concentration of this metal was found in the roots (252 ± 44 mg kg −1 d.w.) and it was distributed within the plant in the following decreasing order: root > stem and leaves > flower. Kickhöfel Ferrer et al [16] found Zn values in roots in a range between 41.3 and 168.8 mg kg −1 d.w. while Demarco et al [23] found concentrations of 235 ± 33 mg kg −1 d.w. in the total plant.…”
Section: Heavy Metals In Plant Tissuementioning
confidence: 98%
See 2 more Smart Citations
“…• Using one or few representative species to draw conclusions about the condition of the whole ecosystem (Markert, 2007) may lead to loopholes in conclusions. Usually, the selection of a bioindicator species is based on its abundance in the region studied (Kickhofel Ferrer et al, 2017) while its accumulation abilities and a clear relation with the pollution of abiotic compartments of a habitat should be the main criteria.…”
Section: Oversimplificationmentioning
confidence: 99%